WAYS OF IMPROVEMENT OF THE ENVIRONMENT CONTROL SYSTEM - A. I. Pankovets; A. V. Rusalenko (Литьë и металлургия)
The ways of improvement of the environment control system are considered. The measures allowing to exclude occurrence of undesirable events are developed under the analysis results.